The effects of industrial development transformation: a geographical perspective study on Kerteh Community, Malaysia - Saudi, Mohd Haizam; Mohd Khori, Shahirah; Kamarudin, Mohd Khairul Amri; Mohd Saudi, Ahmad Shakir; Abu Samah, Mohd Armi; Abdul Maulud, Khairul Nizam; Bati, Siti Nor Aisyah; Mohamad Hamzah, Firdaus; Yaacob, Nur Zafiratul; Mustaffa, Nur Ili Hasmida (Eskisehir Osmangazi University, 2021)
The industrial area of Kerteh was perceived to be rapidly evolving from a fishing village to an urban area. In addition, industrial growth has led to a shift in the living standards of the population and socio-economy, which are the original inhabitants of the city. However, some of the other villages held true to the ideals and customs of the rural society, even as industrial growth was taking place. An effect of this development, the population has been increasing and growing many job opportunities in the industrial sector. From this statement, the researcher had chosen this research to identify the positive and negative impacts of industrial development at Kerteh. Apart from that, the researcher also identified the needs of the respondents according to current developments as well as analyzed the effects of industrial development transformation on Kerteh community. This research conducted using descriptive statistics. The researcher gets the database on the distribution of the questionnaire to 380 respondents around Kerteh as a sample of research. Finding from this study indicates that there has been a shift in the socioeconomic population pattern following the transition of industrial growth at Kerteh, which offers a range of job opportunities. They can also extend the service market, for example, in the business sector. Therefore, this finding will be able to contribute to urban planning such as the development of industries, especially for the Local Authority (PBT) at Kerteh in a sustainable manner.